COMPARATIVE ANALYSIS OF BUDGET IMPLEMENTATION PERFORMANCE OF THE NATIONAL NARCOTICS AGENCY IN THE BALI REGION - Saputra, Made Dwi Widya; Purbawangsa, Ida Bagus Anom (PT Naureen Digital Education, 2024)
The aim of this research is to determine the quality of National Narcotics Agency budget implementation for the Bali Region as well as strategies for improving budget implementation performance. The research data collection method used document observation and interviews conducted with 23 (twenty-three) National Narcotics Agency financial management officials for the Bali Region. The sample determination method is total sampling or saturated sampling. The data analysis technique in this research uses comparative descriptive data analysis techniques regarding the performance of the National Narcotics Agency budget implementation for the Bali Region for 2020-2022. The research results show that in 2020, the quality of budget implementation performance of all National Narcotics Agency work units for the Bali Region was in the good category. In 2021 and 2022 the quality of budget implementation performance will increase to the very good category. The results of the quality of budget implementation exceed the performance targets set in the Performance Agreement. Strategies that can be used to improve budget implementation performance include preparing accurate plans, regular monitoring of budget implementation, reward and punishment, flexibility in budget implementation, good communication and coordination and high commitment. This research provides an illustration that the Bali Region National Narcotics Agency has been able to manage the budget with better budget implementation performance from year to year. Management of state finances should always comply with regulations, be effective and efficient so that it can be beneficial to society in accordance with the goals and ideals of the state.